Performance analysis of membrane separation for upgrading biogas to biomethane at small scale production sites. (September 2019) - Peppers, Joshua; Li, Yin; Xue, Jian; Chen, Xiguang; Alaimo, Christopher; Wong, Luann; Young, Thomas; Green, Peter G.; Jenkins, Bryan; Zhang, Ruihong; Kleeman, Michael J.
Abstract: A small-scale, transportable membrane upgrading system designed to purify biogas was tested at two food waste digesters and one dairy digester. The system had a rated capacity of 100 Nm 3 h −1 raw biogas making it suitable for the many small-scale biogas production facilities being developed across California. The membrane removed a majority of the carbon dioxide from the biogas with performance matching expected targets. The membrane system also removed trace levels of aldehydes, ketones, siloxanes, halocarbons, and sulfur-containing compounds from the biogas, mainly because the pre-cleaning steps removed these contaminants from the gas stream. The average composition of upgraded biomethane produced by the membrane system satisfied the trace contaminant requirements for pipeline injection in California. Residual air in the biogas was not removed efficiently by the membrane system which prevented methane concentrations from reaching levels sufficient to meet the heating value requirements for pipeline injection. Dedicated upgrading plants could carefully eliminate air leakage to address this issue, and/or mix propane into the biomethane to achieve the target heating value. An economic model developed for small scale biogas production facilities predicted that capital costs for a typical small-scale membrane separation plant exceed $2.46 million and projects only become financially viable over a 15 year return period when natural gas prices exceed $21.92 GJ −1 . Current market prices for petroleum natural gas are far below this level, and so financial incentives will be required to make small-scale biogas projects using membrane separation technology viable in the near term. Highlights: A small-scale membrane separation unit was tested for biogas upgrading in California. Pre-cleaning steps removed most trace contaminants but breakthrough occurred. Air injection used at most sites prevented upgrading gas to pipeline quality. Upgrading at small-scales requires subsidies to be economically feasible.